A Study of New Type of Minimal Open and Maximal Closed Sets: Halgwrd Mohammed Darwesh - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we show that the notions of maximal feebly open and minimal feebly closed sets are nothing except maximal α-open and minimal α-closed sets. Further, we show that the ideas of minimal feebly open and maximal feebly closed sets coincide with minimal open and maximal closed sets. Therefore, we introduce new notions of minimal open and maximal closed sets, namely f-minimal open and f-maximal closed sets, some of their properties, characterizations, and relationships established.